Unemployment an Unauthorized Unique Road about Apathy and Poverty the Macedonian Man without Knowledge and Skills - Ljupco, Naumovski; Jasminka, Naumovska (International Research Journal of Management, IT & Social Sciences, 2017)
The topic was aimed at debating the reality that Macedonia as a welfare state and unemployment, ie poverty, constitutional freedom and the right to seek or work to protect from poverty. Aim was the different directions to the concepts of anomalies: unemployment, apathy, poverty, and knowledge related to the concept - Macedonian social state...